(х-3)(3+х)+(х-3)^2 упростить

alexandra171717 alexandra171717    1   12.02.2021 15:04    0

Ответы
Деп567 Деп567  12.02.2021 15:10

2x² - 6x

Объяснение:

(х - 3)(3 + х) + (х - 3)² = (x - 3)(x + 3) + (x - 3)² = x² - 9 + (x² - 6x + 9) = x² - 9 + x² - 6x + 9 = 2x² - 6x

ФСУ, которые были применены:

(a + b)(a - b) = a² - b²

(a - b)² = a² - 2ab + b²

ПОКАЗАТЬ ОТВЕТЫ
zska25 zska25  12.02.2021 15:10

в закрепе

Объяснение:


(х-3)(3+х)+(х-3)^2 упростить​
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра